Resistant dextrin improves high-fat-high-fructose diet induced insulin resistance - Hu, Fan (Nutr Metab (Lond), 2020)
BACKGROUND: Insulin resistance is an important defect associated with obesity and type 2 diabetes mellitus. Many studies have been reported that dietary fiber exerts beneficial metabolic effects. Resistant dextrin is a soluble fiber. The aim of this study was to investigate the effects of resistant dextrin on high-fat-high-fructose diet induced obese mice and to explore the underlying mechanisms. METHODS: Seventeen 4-week-old male C57BL/6 J mice were fed a normal diet (ND) or HFHFD for 22 weeks, and were gavaged with resistant dextrin (5 g/kg) for 10 weeks. Glucose tolerance test (GTT) and insulin tolerance test (ITT) were performed, serum fasting insulin (FINS) and serum biochemical parameters were determined, the contents of triglyceride (TG) and total cholesterol (TC) in liver tissues were determined by enzymatic method. The pathological changes in liver were detected by HE staining. Real time PCR and Western blot were used to detect the expression of insulin signaling pathway and the fatty acid β oxidation pathway related genes and proteins respectively. The gut microbiota were analyzed via 16 s rRNA sequencing. RESULTS: Resistant dextrin significantly decreased serum FINS, improved serum lipid profiles, reduced the contents of liver TG and TC. The insulin signaling pathway and the fatty acid β oxidation pathway were promoted. The abundance of metabolically beneficial bacteria such as Prevotella and Akkermansia in the intestinal flora of the resistant dextrin group were increased. CONCLUSIONS: Resistant dextrin can significantly ameliorate liver insulin resistance, improve serum lipid levels, as well as reduce hepatic lipid deposition. The modulation of gut microbiota might be responsible for the beneficial effects of resistant dextrin.